P-013 Endovascular intervention for acute cerebral ischemia: 13-year single-institution experience. (12th July 2011) - Toy, B; Smith, W; English, J; Halbach, V; Hetts, S
Abstract : Purpose: To characterize clinical, radiological, treatment, and outcome data in patients diagnosed with acute ischemic stroke or transient ischemic attack who underwent emergent endovascular intervention at a single tertiary care institution. Methods: Patients undergoing endovascular intervention for acute ischemic stroke or transient ischemic attack were identified from a neurointerventional database and their medical records retrospectively analyzed. Univariate statistical analysis and logistic regression were performed using custom Matlab scripts. Results: Baseline Characteristics: Between 1997 and 2010, 108 patients underwent endovascular surgery for acute cerebral ischemia. 66 of these patients were treated within 8 h of symptom onset. These patients had a mean age of 66.8±19.5 years (range 5–94); 55% were female. The patients had a baseline modified Ranking score of 1.1±1.2. Cerebrovascular risk factors included: hypertension (63%), dyslipidemia (55%), atrial fibrillation (42%), diabetes mellitus (20%), known cerebrovascular or cardiovascular disease (35%), and current or former smoking (18%). Patients most often presented with motor symptoms (weakness, hemiparesis, hemiplegia—85%), followed by speech difficulty (aphasia or dysarthria—38%), loss of consciousness/altered mental status (28%), and sensory abnormalities (tingling, numbness, dizziness, tinnitis, nausea—9%). 67% of events were witnessed, 23% were unwitnessed, and 6% occurred upon awakening. At presentation, the mean NIH stroke score was 15.3±6.2. Etiology of the events was 83% cardioembolic or thromboembolic, 9% in situ thrombosis, and 8% stenotic. The vessels most often acutely occluded were M1-MCA (56%), M2-MCA (30%), cervical ICA (5%), intracranial ICA (17%), and basilar (17%). Medical Intervention: 37% of patients received intravenous tissue plasminogen activator given at a mean of 2±0.7 h post-ictus; of those who did not (n=38), the most common reason was exceeding the time window for ictus onset to proposed IV-tPA treatment (45%). Endovascular Intervention: All of the patients in this sample underwent at least one endovascular intervention. 53% underwent intra-arterial thrombolysis (mean dose of IA-tPA 8.7±6.2 mg), 76% underwent mechanical thrombectomy (88% MERCI type, 12% Penumbra type), 18% underwent angioplasty (8% extracranial, 92% intracranial), and 15% underwent stenting (20% extracranial, 80% intracranial). 56% of patients were recanalized to TICI 2b or 3, with a mean recanalization time of 7.2±3.2 h. Intra-operative complications included vessel rupture (n=1) and iatrogenic distal large vessel embolization (n=1). 7.6% of patients had evidence of post-op hemorrhagic conversion on follow up head CT. Outcomes: At discharge, mean NIH-SS was 9.6±7.6, and mean mRS was 4±1.7. When subdividing based on intervention type, significant differences were found for post-treatment mRS (p=0.03, Kruskal-Wallis), change in mRS (p=0.01), and change in NIH-SS (p=0.01). At an average of 5.9±7.9 months of follow-up, mean NIH-SS was 3.3±3.2, and mean mRS was 2.4±1.5). When subdividing based on intervention type, significant differences were found for change in mRS (p=0.03), and change in NIH-SS (p=0.002). Conclusion: Endovascular interventions for cerebral ischemia are useful tools in the treatment of acute cerebral ischemia. The difference in clinical outcomes based on intervention subgroups may be associated with the adoption of newer therapeutic modes and warrants further investigation.